Differences in Student Reading Competence at Different Age Periods - Malahova, Ludmila; Budviķe, Inta; Boge, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Development of modern technologies has affected peoples’ reading competence, as a reader today reads not only printed texts in books, magazines and newspapers, but more and more uses texts from the Internet or hypertexts which require new reading strategies. Considering this, we found out, how these changes have affected students’ reading competence at different age periods, in order to use the obtained information for further development of foreign language study courses.